“Belanda Setan” Enters Hiang: The Dutch East Indies Government's Invasion of Kerinci in 1903 - Hudaya, Padhil (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Kerinci was an area that was not touched by the Dutch East Indies Government. The Dutch East Indies government initially tried to